Deletion of Maged1 in mice abolishes locomotor and reinforcing effects of cocaine. (13th July 2018) - De Backer, Jean‐François; Monlezun, Stéphanie; Detraux, Bérangère; Gazan, Adeline; Vanopdenbosch, Laura; Cheron, Julian; Cannazza, Giuseppe; Valverde, Sébastien; Cantacorps, Lídia; Nassar, Mérie; Venance, Laurent; Valverde, Olga; et al.
Abstract: Melanoma antigen genes (Mage) were first described as tumour markers. However, some of Mage are also expressed in healthy cells where their functions remain poorly understood. Here, we describe an unexpected role for one of these genes, Maged1, in the control of behaviours related to drug addiction. Mice lacking Maged1 are insensitive to the behavioural effects of cocaine as assessed by locomotor sensitization, conditioned place preference (CPP) and drug self‐administration. Electrophysiological experiments in brain slices and conditional knockout mice demonstrate that Maged1 is critical for cortico‐accumbal neurotransmission. Further, expression of Maged1 in the prefrontal cortex (PFC) and the amygdala, but not in dopaminergic or striatal and other GABAergic neurons, is necessary for cocaine‐mediated behavioural sensitization, and its expression in the PFC is also required for cocaine‐induced extracellular dopamine (DA) release in the nucleus accumbens (NAc). This work identifies Maged1 as a critical molecule involved in cellular processes and behaviours related to addiction. Synopsis: Identification of genes underlying physiological changes induced by drugs of abuse provides molecular insight into addiction. This study reveals that Maged1 is required for the expression of behavioural effects of cocaine in mice. Mice lacking Maged1 are insensitive to the locomotor, rewarding and reinforcing effects of cocaine. Cocaine‐induced dopamine overflow in the striatum is impaired in mice lacking Maged1. Conditional Maged1 deletion in the prefrontal cortex selectively impairs locomotor sensitization to cocaine and cocaine‐induced dopamine overflow. Abstract : Identification of genes underlying physiological changes induced by drugs of abuse provides molecular insight into addiction. This study reveals that Maged1 is required for the expression of behavioural effects of cocaine in mice.